Effects of dietary supplementation with essential oils and organic acids on the growth performance, immune system, fecal volatile fatty acids, and microflora community in weaned piglets. (2nd November 2018) - Yang, Caimei; Zhang, Lingling; Cao, Guangtian; Feng, Jie; Yue, Min; Xu, Yinglei; Dai, Bin; Han, Qianjie; Guo, Xiqin
Abstract: The present study was conducted to assess the effects of a mixture of essential oils and organic acids on the growth performance, immune system, major fecal volatile fatty acids (VFAs), and microflora community in the weaned piglets. We also evaluated the antibacterial activity of the essential oil mixture on Escherichia coli and Staphylococcus aureus . Three hundred weaned piglets (Duroc × Landrace × Yorkshire) were randomly divided into the following 3 treatment groups: basal diet (C), basal diet supplemented with the mixture of essential oils and organic acids (T1), and basal diet supplemented with antibiotics (T2). The mixture of essential oils and organic acids comprised of cinnamaldehyde (15%), thymol (5%), citric acid (10%), sorbic acid (10%), malic acid (6.5%), and fumaric acid (13.5%). In vitro studies showed that the mixture of essential oils extremely damaged the cell structure of pathogenic bacteria by deforming the membranes and disorganizing the intracellular components. In vivo studies revealed that diet supplementation with a mixture of essential oils and organic acids improved the final body weight and ADG of piglets ( P < 0.05), increased the concentration of serum complement 4 ( P < 0.05), and enhanced the fecal level of isovaleric acid ( P < 0.05) compared with controls on day 28. Result of high-throughput sequencing revealed that: 1) a total of 1, 177 and 1, 162 observed taxonomic units (OTUs) were shared between all treatment groups on day 14 and 28, respectively; 2) the T1 exhibited higher ( P < 0.05) beta diversity (unweighted UniFrac distance) than control and antibiotics treatment on day 28; 3) the samples in principle component analysis plot and tree of relative abundance were separated from each other based on dietary treatments and age; 4) Firmicutes and Bacteroidetes were the most 2 dominate phyla; Lactobacillus and Streptococcus were the 2 top species among the recognized microbiota; 5) T1 had higher ( P < 0.05) relative abundance of Lactobacillus mucosae than control and antibiotics treatment on day 28. To conclude, the mixture of cinnamaldehyde and citric acids damaged the structure of pathogens in vitro; the mixture of essential oils and organic acids improved the growth performance, increased the fecal concentration of isovaleric acid, and modulated the microflora community in weaned piglets.